The French language in Russia : a social, political, cultural, and literary history - Offord, Derek; Rjéoutski, Vladislav; Argent, Gesine (Languages and culture in history, 2018)
The French Language in Russia' provides the fullest examination and discussion to date of the adoption of the French language by the elites of imperial Russia during the eighteenth and nineteenth centuries. It is interdisciplinary, approaching its subject from the angles of various kinds of history and historical sociolinguistics. Beyond its bearing on some of the grand narratives of Russian thought and literature, this book may afford more general insight into the social, political, cultural, and literary implications and effects of bilingualism in a speech community over a long period. It should also enlarge understanding of francophonie as a pan-European phenomenon. On the broadest plane, it has significance in an age of unprecedented global connectivity, for it invites us to look beyond the experience of a single nation and the social groups and individuals within it in order to discover how languages and the cultures and narratives associated with them have been shared across national boundaries.